“Gente, o que é macumba?”: sentidos e significados construídos acerca das religiões de matrizes africanas - Silva, Cintia Quina Da [UNIFESP] (2020)
Nowadays the issue that involves differences of race and religiosity has gained space in research in the field of education. The school context can be characterized as an important locus of understanding of social relations that occur in racial and religious diversity. In this sense, this study aimed to understand how school interactions occur among girls who are adepts and non-adepts of religions of African origin. Seeking to achieve this goal, the methodology of this qualitative research included participant observation techniques, group interviews with high school girls, in addition to interviews with teachers and managers of a school in a city in the greater São Paulo. Based on an analysis based on historical-cultural theory, the objective was to understand how mediations between these young women and adults occur in line with the positions adopted and the reflections built in facing and fighting ethnic-racial inequalities in school spaces. The analysis showed that part of this process occurs, mainly due to the structural racism that is expressed in different ways and in all areas of social life with the school being an institution with a strong role in this process.